Long-term treatment outcomes from the perspective of a patient with unilateral cleft lip and palate. Issue 12 (30th December 2021) - Fowler, Peter; Ardouin, Kenny; Haworth, Jennifer; Snape, Leslie
Abstract : The management of patients with orofacial cleft (OFC) often extends from diagnosis or birth well into adulthood and requires many different specialists within multidisciplinary teams (MDT). The aims of treatment are to restore form and function relating to hearing, speech, occlusion and facial aesthetics. People with OFCs that include the lip, alveolus and palate (cleft lip and palate (CLP)) require several different staged and coordinated surgical and non-surgical interventions, and the treatment pathway is associated with a heavy burden of care. Due to the extensive nature of the interaction with these patients, MDT members have opportunities to provide enhanced patient-centred care and support. This case report provides an overview of the current knowledge of the aetiology of OFC and the management of these patients. It provides a unique perspective from one of the coauthors who has a unilateral CLP (UCLP) and reports on his treatment experiences and long-term treatment outcomes. By having a better understanding of the impact of UCLP and treatment provided, MDT members can not only provide improved clinical treatment but also offer improved patient experiences for those with craniofacial anomalies, in particular, an increased awareness of the psychosocial challenges, they endure throughout their treatment pathway and beyond.